Evaluation of the Performance of Techniques to Transmit IPv6 Data through IPv4 Networks - Gelvez García, Nancy Yaneth; Sánchez Céspedes, Juan Manuel; Herrera Cubides, Jhon Francined (TECCIENCIA, 2013)
This article presents the simulation of an IPv4 network connected to two IPv6 isles. Those protocols are not compatible; therefore, transition mechanisms were implemented to fulfill a fundamental role. Meanwhile, this reaches the total deployment of IPv6, such as: Tunneling and Address translation. The first, encapsulates an IPv6 packet inside an IPv4 Header so that it can be moved through the network; the second, translates the address and the protocol of those packets crossing through it. To assess the performance of each technique when the data is sent, the changes with respect to memory consumption and router processing were analyzed.